How to Deal with Really Good Bad-Faith Interpreters: M.A. v Denmark - Molbæk-Steensig, Helga (Utrecht Journal of International and European Law, 2022)
Can a State that no-longer officially pursues an integration agenda for a group of refugees claim integration as a legitimate aim to interfere with the fundamental rights of said group? If domestic courts’ careful consideration of international human rights law and practice widens the State’s margin of appreciation, is it then narrowed when States ignore national and international organisations’ warnings of non-compliance with human rights law? Can the European Court of Human Rights refer to EU-law to establish the existence of a European consensus when the respondent State in question has opted out of EU-regulation in the area? The Grand Chamber judgment M.A. v Denmark from 9 July 2021 raises these questions but answers only some. This article aims, through an analysis of M.A. v Denmark and its political and legal background, to seek some answers in this carefully worded judgment.